2011
DOI: 10.1073/pnas.1017667108
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer cell-derived microvesicles induce transformation by transferring tissue transglutaminase and fibronectin to recipient cells

Abstract: Tumor progression involves the ability of cancer cells to communicate with each other and with neighboring normal cells in their microenvironment. Microvesicles (MV) derived from human cancer cells have received a good deal of attention because of their ability to participate in the horizontal transfer of signaling proteins between cancer cells and to contribute to their invasive activity. Here we show that MV may play another important role in oncogenesis. In particular, we demonstrate that MV shed by two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
515
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(530 citation statements)
references
References 29 publications
14
515
0
1
Order By: Relevance
“…Exosomes are thus believed to have the potential to serve as shuttles for intercellular communication. 8,31 This may be highly relevant for carcinogenesis, and reported effects for tumor cell-derived exosomes range from inhibition of antitumor immune response 9,45 to the horizontal transfer of oncogenic factors, 11,15,50,51 induction of angiogenesis 11,48 and promotion of premetastatic niche formation. 52 Although these observations are potentially extremely important, one must be aware that most studies performed thus far used concentrated exosome preparations, and it is not clear how these experimental …”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are thus believed to have the potential to serve as shuttles for intercellular communication. 8,31 This may be highly relevant for carcinogenesis, and reported effects for tumor cell-derived exosomes range from inhibition of antitumor immune response 9,45 to the horizontal transfer of oncogenic factors, 11,15,50,51 induction of angiogenesis 11,48 and promotion of premetastatic niche formation. 52 Although these observations are potentially extremely important, one must be aware that most studies performed thus far used concentrated exosome preparations, and it is not clear how these experimental …”
Section: Discussionmentioning
confidence: 99%
“…Although these classical events have been commonly thought of as the predominant modes of cell-to-cell communication, a novel type of vesicle secretion has recently received a great deal of attention [8,9,15,33] . Though the secretion of exosomes by myeloma [21,34] , there have been no previous studies about MM-MVs.…”
Section: Discussionmentioning
confidence: 99%
“…MVs can reach the local target cells but can also travel over long dis tances [12,13] . A large number of studies have reported that tumor cellderived MVs (TMVs) reflect the special potential of tumor cells for the expansion of the tumor, independently from cell to cell contact [14,15] . Recently, a growing body of evidence suggests that TMVs contain a selective enrichment of a discrete set of cellular molecules that can be transferred into the target cells [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…GBM is the most common primary malignant tumour of the central nervous system in adults and known to release large amounts of EVs [10,35,36]. Affected patients have an extremely poor prognosis with a median survival of only 15 months following treatment [37].…”
Section: Introductionmentioning
confidence: 99%